Insight into the SEA amide thioester equilibrium. Application to the synthesis of thioesters at neutral pH. Issue 30 (10th June 2016) - Pira, S. L.; El Mahdi, O.; Raibaut, L.; Drobecq, H.; Dheur, J.; Boll, E.; Melnyk, O.
Abstract : Peptide alkylthioesters can be prepared at neutral pH by bis (2-sulfanylethyl)amide-thiol exchange. Abstract : The bis (2-sulfanylethyl)amide (SEA) N, S -acyl shift thioester surrogate has found a variety of useful applications in the field of protein total synthesis. Here we present novel insights into the SEA amide/thioester equilibrium in water which is an essential step in any reaction involving the thioester surrogate properties of the SEA group. We also show that the SEA amide thioester equilibrium can be efficiently displaced at neutral pH for accessing peptide alkylthioesters, i.e. the key components of the native chemical ligation (NCL) reaction.